Achieving Equilibrium in Ayurveda: The Role of Dosha, Dhatu, and Mala in Promoting Wellness (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda, the oldest Indian medicine system, focuses on the balance of Dosha (bio-energies), Dhatu (tissues), and Mala (waste products)- the essences of which is critical to the health. The article explores prerequisites for health in Bharatiya (Indian) lifestyle - Samyata (equilibrium) of Dosha (Vata, Pitta, Kapha), Dhatu (seven bodily tissues) and Mala (urine, feces, sweat). This study narratively reviews classical Ayurvedic texts and modern interpretations to illustrate their roles and interrelationships as well as practical strategies for maintaining equilibrium. The results emphasize that lifestyle factors, which include diet (Ahara), daily routine (Dinacharya) and mental well-being (Manas) are essential to achieving Samyata. These principles, still relevant in our contemporary health discourse, provide a guide to holistic preventive and therapeutic care. This research validates Ayurveda’s eternal principles for sustainable well-being.